2021
DOI: 10.22617/tcs210400-2
|View full text |Cite
|
Sign up to set email alerts
|

Global Value Chain Development Report 2021:

Abstract: Creative Commons Attribution-NonCommercial 3.0 IGO license (CC BY-NC 3.0 IGO) © 2021 asian Development bank, Research institute for Global Value Chains at the university of international business and economics, the World trade organization, the institute of Developing economies -Japan external trade organization, and the China Development Research Foundation. iSbn 978-92-9269-090-8 (print); 978-92-9269-091-5 (electronic); 978-92-9269-092-2 (ebook) publication Stock no. tCS210400-2 Doi: http://dx.doi.org/10.226… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…The structure of networks determines potential GVC vulnerabilities and propensity to amplify shocks. Network analysis helps identify the importance of a country or sector in the GVC networkthe so-called centralityby accounting for the direct participation of countries in GVCs and also for the participation of their value-chain partners (Criscuolo and Timmis, 2018 [36]; Cingolani, Iapadre and Tajoli, 2018 [37]; Altomonte, Colantone and Bonacorsi, 2018 [38]; Arriola et al, 2020 [23]). The higher the centrality indicator, the greater the importance of a country/industry as a supplier or customer in the network and the larger potential to propagate shocks.…”
Section: Centrality and Choke Pointsmentioning
confidence: 99%
See 3 more Smart Citations
“…The structure of networks determines potential GVC vulnerabilities and propensity to amplify shocks. Network analysis helps identify the importance of a country or sector in the GVC networkthe so-called centralityby accounting for the direct participation of countries in GVCs and also for the participation of their value-chain partners (Criscuolo and Timmis, 2018 [36]; Cingolani, Iapadre and Tajoli, 2018 [37]; Altomonte, Colantone and Bonacorsi, 2018 [38]; Arriola et al, 2020 [23]). The higher the centrality indicator, the greater the importance of a country/industry as a supplier or customer in the network and the larger potential to propagate shocks.…”
Section: Centrality and Choke Pointsmentioning
confidence: 99%
“…The increasing reliance on intermediate inputs facilitated by GVC integration spurs economic growth, leads to denser production networks and reduces all prices (Acemoglu and Azar, 2020 [59]). According to some simulations, the quantitative effects of higher volatility are not guaranteed and are small in relation to efficiency gains (Arriola et al, 2020 [23]; D'Aguanno et al, 2021 [48]).…”
Section: Shock Propagation and Economic Volatilitymentioning
confidence: 99%
See 2 more Smart Citations
“…During recent decades, emerging inter-regional trade with the expansion of global value chains led to an increasingly complex inter-regional production network. , Entities at different positions along the value chain provide diversified products and services (i.e., raw material and intermediate products for further production, manufacturing, and services for final products) . It is suggested that participating in the value chain promotes social welfare growth (such as higher salary, more job opportunities, and more public revenue) by improving the efficiency and quality of production and supply; , however, the social welfare gains are not allocated evenly among different participants, and varying degree of external losses (e.g., environmental damage) also occur in various production stages, delivering the uneven gains and losses allocation along the value chain.…”
Section: Introductionmentioning
confidence: 99%